Investigation on Mn doping of Ge nanowires for spintronics. Issue 2 (3rd February 2014) - Renard, C.; Vincent, L.; Gardès, C.; Boukhicha, R.; Oliviero, E.; Patriarche, G.; Fossard, F.; Hajjar, S.; Bubendorff, J. L.; Pirri, C.; Bouchier, D.
Abstract Various approaches are described to synthesize Mn‐doped Ge NWs using UHV‐CVD growth via the VLS mechanism. We explored in‐situ doping using an organo‐metallic precursor (TCMn) and tested different catalyst seeds such as Au, Au‐Mn or Ge‐Mn. All in‐situ attempts failed to incorporate Mn atoms into the NW. Moreover we observed that the use of TCMn and/or Au‐Mn catalysts have a crippling effect on the growth kinetics. Finally, ex‐situ doping with ion implantation is right now considered as a doping alternative. We report on preliminary results aiming at testing the radiation resistance of Ge NWs embedded in a removable silica matrix. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)